Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together untuk Meningkatkan Hasil Belajar Siswa pada Materi Menghargai Peninggalan Sejarah di MIS Al-Hidayah - Siti Rahmadani Harahap (LP3M KH Yazid Karimullah Institute, 2024)
This research aims to improve student learning outcomes in the material of appreciating historical heritage through the application of the Numbered Head Together (NHT) type cooperative learning model at MIS Al-Hidayah Namorambe. The NHT learning model is one of the cooperative learning strategies that involves the active participation of students in groups. In this process, each student is assigned a number and takes turns answering questions asked by the teacher. This approach aims to improve student understanding, participation, and learning outcomes.The research method used is classroom action research (PTK) which is carried out in two cycles. Each cycle consists of the stages of planning, implementation of actions, observation, and reflection. Data was collected through learning outcome tests and observation of student activities. The results of the study showed a significant increase in student learning outcomes after the implementation of the NHT model. In addition, the application of this model also increases learning motivation and cooperation between students in groups. The conclusion of this study is that the NHT-type cooperative learning model is effective in improving student learning outcomes on the material of appreciating historical heritage. Therefore, this model is recommended to be used as an alternative learning strategy in history subjects in elementary schools.